Optimalisasi Program K3 di Area Gudang Penyimpanan Melalui Pendekatan HIRADC Pada PT XYZ - Arya Dany Ardhiansah; Tranggono (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The implementation of health, safety and environment (HSE) programmes is crucial in industrial operations, especially in warehouses, which are high-risk areas for industrial accidents. This study focuses on optimising the HSE programme in the warehouse of a steel pipe manufacturing plant in East Java using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. The HIRADC approach systematically identifies potential hazards, assesses risk levels and determines appropriate control measures to minimise risks. The study identified significant risks associated with pipe loading and unloading activities, such as falling pipes and equipment malfunctions. Control measures, including the installation of safety signage, preventive maintenance, crane use and the use of personal protective equipment, were implemented to reduce the risks. The study concludes that the implementation of HIRADC is effective in reducing risks and creating a safer working environment.